Nature of adolescent role models on female construction management professionals - Loughmiller, Katie (Crawford) (Kansas State University, 2024)
The underrepresentation of women in the construction management field over the past decades remains a persistent issue. This research addresses the relatively unexplored area of role model relationships established by female construction managers during their formative years and how these connections impact their career choices. The study investigates the influence of relationships formed with adults during adolescence on success in construction management careers, focusing on the Ethic of Care theory. Three key research questions are explored: the identification process of role models, the timing of these connections in participants' adolescent years, and the correlation between these relationships and career choices considering societal and cultural influences. The research methodology employs narrative inquiry, allowing participants to share their experiences through semi-structured interviews. Seven female participants were selected from responses to a questionnaire distributed via the National Association of Women in Construction. The presentation of data from the semi-structured interviews was conducted in two formats. First, the data was presented through the creation of a short story intertwining the stories of the seven interview participants. Second, the data was presented using traditional methods, identifying eight themes, aligned with the research questions. The findings provide insight into the benefits of role-model relationships during adolescence and the lack of exposure to educational and career opportunities in the construction industry during middle and high school.
Keywords: Construction management; Construction education; Role model; Mentor; STEM